BIOM-23. MOLECULAR MARKER TESTING AND REPORTING COMPLETENESS FOR ADULT-TYPE DIFFUSE GLIOMAS IN THE UNITED STATES. (14th November 2022) - Neff, Corey; Cioffi, Gino; Waite, Kristin; Kruchko, Carol; Barnholtz-Sloan, Jill; Ostrom, Quinn; Iorgulescu, Bryan
Abstract: BACKGROUND: A newly developed brain molecular marker (BMM) data item was implemented by U.S. cancer registries for individuals diagnosed with brain tumors in 2018—including IDH and 1p/19q-codeletion statuses for adult-type diffuse gliomas. We thus investigated the testing/reporting completeness of BMM in the U.S. METHODS: Cases of histopathologically-confirmed glioblastoma, astrocytoma, and oligodendroglioma diagnosed in 2018 were identified in the National Cancer Database. Adjusted odds ratios (ORadj ) and 95% confidence intervals (95CI) of BMM testing/reporting were evaluated for association with selected patient, treatment, and facility-level characteristics using multivariable logistic regression. As a secondary analysis, predictors of MGMT promoter methylation testing/reporting among IDH-wildtype glioblastoma individuals was assessed. RESULTS: Among 7, 370 histopathologically-diagnosed adult-type diffuse gliomas nationally, the overall BMM testing/reporting completeness was 81%. Compared to biopsy-only cases, the odds of testing/reporting increased for increased for subtotal (ORadj = 1.38 [95CI: 1.19-1.61], p< 0.001) and gross total resection (ORadj =1.53 [95CI: 1.33-1.77], p< 0.001). Furthermore, the odds of testing/reporting completeness were lowest at community centers (hospitals (65.8%; ORadj =0.33 [95CI: 0.24-0.44], p< 0.001) and highest at academic/NCI-designated comprehensive cancer centers (85.3%; referent). By geographical location, BMM testing/reporting completeness ranged from a high of 86.9% at New England (referent) to a low of 75.2% in the West South Central region (ORadj=0.55 [95CI: 0.39-0.76]; p< 0.001). Extent of resection, facility type, and facility location were additionally significant predictors of MGMT testing/reporting among IDH-wildtype glioblastoma cases. CONCLUSION: Initial BMM testing/reporting completeness for individuals with adult-type diffuse gliomas in the U.S. were favorable, although patterns varied by hospital attributes and extent of resection.